2021
DOI: 10.1007/s12603-021-1616-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions for Early Dementia

Abstract: Nutrition plays a critical role in the definition of the individual’s wellbeing. Nutritional interventions have been repeatedly advocated as of potential interest for preventing or delaying the cognitive decline, also in the context of neurodegenerative conditions. The idea of targeting the initial phases of dementia, when the process is theoretically still amenable of correction, via lifestyle modifications (including healthy diet or supplementation of specific micro-/macro-nutrients) is extremely appealing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“… 9 However, inconsistent results have also been reported that nutritional supplements did not improve cognitive function in older adults who were malnourished, 10 and persons with MCI may not present major differences in nutritional status compared to healthy individuals. 11 Therefore, the association between malnutrition and cognitive function needs to be further evaluated.…”
Section: Introductionmentioning
confidence: 99%
“… 9 However, inconsistent results have also been reported that nutritional supplements did not improve cognitive function in older adults who were malnourished, 10 and persons with MCI may not present major differences in nutritional status compared to healthy individuals. 11 Therefore, the association between malnutrition and cognitive function needs to be further evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For their mental health, perceived quality of life, cognition, and psychological wellness can be measured (3). In addition to nutritional care, individuals can benefit from exercise or physical activity programs, cognitive care, and encouragement of social connections (79)(80)(81)(82). For healthcare systems, nutritional interventions for care of older people can also be measured in terms of resource use, cost savings, and cost-effectiveness.…”
Section: How Can Healthcare Professionals Monitor the Effectiveness O...mentioning
confidence: 99%
“…It also serves an important role in the onset and prognosis of dementia ( Brockdorf and Morley, 2021 ). As such, nutritional assessment and intervention provides rich potential when nested within a comprehensive integrative approach to dementia care ( Cesari et al, 2021 ). When overlooked, a vicious cycle may present as cognitive decline affects nutritional status, and malnutrition in turn worsens cognitive decline ( Cesari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, nutritional assessment and intervention provides rich potential when nested within a comprehensive integrative approach to dementia care ( Cesari et al, 2021 ). When overlooked, a vicious cycle may present as cognitive decline affects nutritional status, and malnutrition in turn worsens cognitive decline ( Cesari et al, 2021 ). Indeed, even the most well-designed pharmaceutical will fail in the face of unmet needs that are fundamental to healthy living, such as social interaction, physical activity, and a healthy diet ( Cesari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation